SDSS J114818.18-013823.7: Forming Compact Dwarf Galaxy through the Dwarf-Dwarf Merger (Journal of Nepal Physical Society, 2021)
We studied the spectroscopic properties of the low redshift (z = 0.0130) interacting dwarf galaxy SDSS J114818.18-013823.7. It is a compact galaxy of half-light radius 521 parsec. It’s r-band absolute magnitude is -16.71 mag. Using a publicly available optical spectrum from the Sloan Sky Survey data archive, we calculated star-formation rate, emission line metallicity, and dust extinction of the galaxy. Star formation rate (SFR) due to Hα is found to be 0.118 Mʘ year-1 after extinction correction. The emission-line metallicity, 12+log(O/H), is 8.13 dex. Placing these values in the scaling relation of normal galaxies, we find that SDSS J114818.18-013823.7 is a significant outlier from both size-magnitude relation and SFR-B-band absolute relation. Although SDSS J114818.18-013823.7 possess enhance rate of star-formation, the current star-formation activity can persist several Giga years in the future at the current place and it remains compact.